Occurrence of Sex Chromosomes in Fish of the Genus Ancistrus with a New Description of Multiple Sex Chromosomes in the Ecuadorian Endemic Ancistrus clementinae (Loricariidae) - Nirchio, Mauro; Oliveira, Claudio [UNESP]; de Bello Cioffi, Marcelo; de Menezes Cavalcante Sassi, Francisco; Valdiviezo, Jonathan; Paim, Fabilene Gomes; Soares, Leticia Batista; Rossi, Anna Rita (MDPI, 2023)
Ancistrus Kner, 1854, is the most diverse genus among the Ancistrini (Loricariidae) with 70 valid species showing a wide geographic distribution and great taxonomic and systematic complexity. To date, about 40 Ancistrus taxa have been karyotyped, all from Brazil and Argentina, but the statistic is uncertain because 30 of these reports deal with samples that have not yet been identified at the species level. This study provides the first cytogenetic description of the bristlenose catfish, Ancistrus clementinae Rendahl, 1937, a species endemic to Ecuador, aiming to verify whether a sex chromosome system is identifiable in the species and, if so, which, and if its differentiation is associated with the presence of repetitive sequences reported for other species of the family. We associated the karyotype analysis with the COI molecular identification of the specimens. Karyotype analysis suggested the presence of a ♂ZZ/♀ZW1W2 sex chromosome system, never detected before in Ancistrus, with both W1W2 chromosomes enriched with heterochromatic blocks and 18S rDNA, in addition to GC-rich repeats (W2). No differences were observed between males and females in the distribution of 5S rDNA or telomeric repeats. Cytogenetic data here obtained confirm the huge karyotype diversity of Ancistrus, both in chromosome number and sex-determination systems.
Keywords: Ancistrini; Hypostominae; rDNA; teleost; telomeric repeats; ZZ/ZW1W2 sex system